2012
DOI: 10.12693/aphyspola.121.647
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Methods of Speciation Using X-ray Absorption Fine Structure

Abstract: Determination of the chemical forms along with the relative quantity of the dierent species in a given sample, termed as speciation, can be done by analyzing X-ray absorption ne structure spectra. The dierent methods that can be used for speciation are: principal component analysis, target transformation, methods based on derivative spectra, method based on the relative position of the absorption edge, residual phase analysis, normalized dierence absorption edge spectra analysis and linear combination tting. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
3
38
0
1
Order By: Relevance
“…The co-presence of Cu 2 O and CuO, with different percentages and in particular with a relevant presence of Cu 2 O, can be identified in the near edge region by a lowering of the intensity of the absorption peak B. [42] This effect can clearly be observed in Figs 2 and 3. It is well known that also NPs size effects can induce changes in the near edge region, but we surely cannot exclude that, the observed lowering of the intensity of the peak B, does not include also a contribution coming from the presence of a CuO surface layer.…”
Section: Structural Characterizationmentioning
confidence: 86%
“…The co-presence of Cu 2 O and CuO, with different percentages and in particular with a relevant presence of Cu 2 O, can be identified in the near edge region by a lowering of the intensity of the absorption peak B. [42] This effect can clearly be observed in Figs 2 and 3. It is well known that also NPs size effects can induce changes in the near edge region, but we surely cannot exclude that, the observed lowering of the intensity of the peak B, does not include also a contribution coming from the presence of a CuO surface layer.…”
Section: Structural Characterizationmentioning
confidence: 86%
“…Referring to the observed systematic changes of the spectra with composition we made an attempt to represent the EXAFS oscillations of the alloys as a weighted sum of the spectra for the end compounds: CZTS and CZTSe. We applied the LCF method that is used to determine relative amount of known constituents in complex systems . The LCF fitting has been done using the Cu, Zn and Sn EXAFS oscillations χ(k) in the k ‐space range (2.0–12.0) Å −1 for CZTS and CZTSe compounds: χalloy(k)=(1xfit)χCZTS(k)+xfitχCZTSe(k) …”
Section: Resultsmentioning
confidence: 99%
“…We applied the LCF method that is used to determine relative amount of known constituents in complex systems. [24,25] The LCF fitting has been done using the Cu, Zn and Sn EXAFS oscillations χ(k) in the k-space range (2.0-12.0) ÅÀ 1 for CZTS and CZTSe compounds:…”
Section: Resultsmentioning
confidence: 99%
“…LCF of As/Mg-Al-LDH and HNa 2 AsO 4 As K-edge XANES to model the coprecipitated sample spectra (results listed in Table 2) also indicated that all samples primarily consisted of one component, As/Mg-Al-LDH. In addition, the relative amount of As/Mg-Al-LDH increased from the samples aged for 5d to samples aged for 180d [36]. 10 Being the major component of all the investigated samples, the As/MgAl-LDH EXAFS spectrum was fit to the EXAFS equation to characterise its coordination structure.…”
Section: Xas Analysesmentioning
confidence: 99%